2018
DOI: 10.1002/jez.2181
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of developmental plasticity in response to incubation temperature in reptiles

Abstract: Early life environments shape phenotypic development in important ways that can lead to long-lasting effects on phenotype and fitness. In reptiles, one aspect of the early environment that impacts development is temperature (termed 'thermal developmental plasticity'). Indeed, the thermal environment during incubation is known to influence morphological, physiological, and behavioral traits, some of which have important consequences for many ecological and evolutionary processes. Despite this, few studies have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 132 publications
(197 reference statements)
3
88
1
Order By: Relevance
“…Thus, detecting within‐ and among‐population variation in important traits is key for understanding if, and how, species can respond to temporal or spatial environmental shifts. Within the context of contemporary climate change, thermally mediated traits are of particular importance (Kingsolver, Diamond, & Buckley, ; While et al, ). The ideal model trait for examining the intraspecific and interspecific effects of thermal heterogeneity is (a) fundamental to organismal physiology, (b) directly impacted by temperature in at least one measurable way, (c) intrinsically involved with key processes that extend beyond the trait itself and (d) subject to biologically significant, contemporary variation in thermal conditions (Angilletta, ; Kingsolver et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, detecting within‐ and among‐population variation in important traits is key for understanding if, and how, species can respond to temporal or spatial environmental shifts. Within the context of contemporary climate change, thermally mediated traits are of particular importance (Kingsolver, Diamond, & Buckley, ; While et al, ). The ideal model trait for examining the intraspecific and interspecific effects of thermal heterogeneity is (a) fundamental to organismal physiology, (b) directly impacted by temperature in at least one measurable way, (c) intrinsically involved with key processes that extend beyond the trait itself and (d) subject to biologically significant, contemporary variation in thermal conditions (Angilletta, ; Kingsolver et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…During this time, skepticism about TSD in reptiles faded as laboratory and field studies clearly demonstrated this sex‐determining mechanism in many turtles and crocodilians (Bull, ; Bull & Vogt, ; Ferguson & Joanen, ; Pieau, ). Research on TSD has since been the most prominent area of focus in reptilian developmental plasticity (see While et al., ). Further detailed work (Ackerman, ; Packard & Packard, ; Prange & Ackerman, ) firmly established the roles of hydric conditions and gas exchange during egg incubation in shaping physiological and morphological phenotypes of hatchling reptiles.…”
Section: Brief History Of the Fieldmentioning
confidence: 99%
“…Such bias is largely a function of the knowledge available for different taxonomic groups. There are far more studies on relatively short‐lived squamates than on long‐lived chelonians or crocodilians (e.g., While et al., ). Moreover, reviews of reptile developmental plasticity often exclude research on birds (DuRant, Hopkins, Hepp, & Walters, ), despite the fact that birds fall within the reptilian clade and exhibit many similar developmental responses to the environment as nonavian reptiles.…”
Section: Brief History Of the Fieldmentioning
confidence: 99%
“…Temperature can have profound effects on the developmental trajectory of organisms (i.e., thermal developmental plasticity). These effects have been particularly well studied in ectotherms, in which the thermal environment an embryo experiences during development regulates key physiological processes and, through this, a range of phenotypic traits including development rate, morphology, behavior, performance, physiology, and even sex (Shine, Elphick & Harlow, ; Cunningham, While, & Wapstra, ; Pearson & Warner, ; Noble, Stenhouse, & Schwanz, ; While et al., ). Importantly, these effects can have significant consequences for fitness both in the short and the long term (Caley & Swarzkopf, ; Noble et al., ) and can, therefore, affect key evolutionary and ecological processes (Moczeck et al., ; Uller, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are two main reasons for this. First, population‐specific thermal reaction norms of development are relatively poorly characterized, particularly for ectothermic vertebrates such as reptiles (While et al., ). To address this, we must characterize developmental plasticity across (and beyond) the range of temperatures currently experienced by populations in the wild, especially those located at a species’ climatic limits.…”
Section: Introductionmentioning
confidence: 99%